A discourse analysis of advertisements in terms of persuasion strategies in english and vietnamese (Trường Đại học Ngoại ngữ, Đại học Đà Nẵng, 2025)
This is a discourse analysis of advertisements in terms of persuasion strategies in English and Vietnamese. The data for analysis in this thesis are 260 samples of advertisements (130 in English and 130 in Vietnamese) which contain persuasive strategies and are posted on the internet by companies, organizations, groups and individual. The descriptive research is carried out based on the combination of a variety of methods, namely qualitative and quantitative. The study analyzes discourse features of advertisements used with persuasive strategies in English and Vietnamese advertisements in terms of layout, vocabulary, syntax, and pragmatic features. It also makes a comparison to discover the similarities and differences of these features between the two languages. The finding shows that both English and Vietnamese advertisements on the internet display a four-part structure: Headline, Body Copy, Illustration and Standing Details. Vocabulary choices, Sentence types, and voice are prominent grammatical features which were qualitatively and quantitatively analyzed and compared. In addition, commonly used persuasive strategies of advertisements in both English and Vietnamese are also identified. Finally, pragmatic features reveals that representative, commissive and directive are the most prominent devices used in persuasive strategies of advertisements in both English and Vietnamese. On the basis of the findings, some implications for teaching and learning in both languages are suggested. This thesis is significant in providing some linguistic and pedagogical contributions. Linguistically, the study yields a better insight into discourse analysis and advertising in general as well as the discourse features of persuasive strategies used in advertisements in English and Vietnamese in particular. Pedagogically, the research result can be useful for recruiters, copywriters, teachers and learners of English, as well as those who are interested in advertising, especially persuasive strategies of advertisements.